Pengaruh Penggunaan Transtibial Prosthesis Terhadap Citra Tubuh Pasien Pasca Amputasi Transtibial - Muhammad Syaifuddin; Maretania Devi Maya Santi; Prasetyo Catur Utomo (Jurnal Keterapian Fisik, 2019)
Background : Amputation is defined as the act of separating parts of the body in part or all parts of the extremities. Clients post amputation of the lower limbs report social discomfort associated with changes in body image due to the presence of missing body parts and ultimately affect the appearance both psychologically and physically. Transtibial Prosthesis is an intervention in the form of a prosthesis which is paired outside the body in order to restore lost limb shape and can replace the function anatomically and functionally. In this study conducted a test to determine the effect of the use of transtibial prosthesis to the patient's body image after transtibial amputation. Method : This study is Quasy Experimental with one group pre and post test design. The subjects had used transtibial prosthesis from APOC Clinic, Boyolali, Central Java. The location this study in Surakarta. Subjects of this study is 17 people Result : there is an effect of the use of transtibial prosthesis in the form of improved body image for patients post transtibial amputation (wilcoxon test is 0,000 where the P < 0,05). Conclusion : there is an effect of the use of transtibial prosthesis in the form of improved body image for patients post transtibial amputation.